Evolution of magnetic nanophases of Ni embedded in Al2O3 (001) matrix by X-ray magnetic circular dichroism - Thakur, P.; Kumar, Ravi; Cezar, J. C.; Brookes, N. B.; Sharma, Aditya; Arora, S. K.; Gautam, S.; Kumar, Arvind; Chae, K. H.; Shvets, I. V. (ELSEVIER SCIENCE BV, 2011)
We report on the element-specific magnetic characterization of Ni nanoparticles (NPs) embedded in Al2O3 (0 0 1) matrix prepared by ion-implantation (Ni:5 x 10(16)-2 x 10(17) ions cm(-2)) technique. The X-ray diffraction studies reveal the coexistence of fcc Ni NPs of average size similar to 8-19 nm along with the other NiOx phases. X-ray magnetic circular dichroism (XMCD) experiments demonstrate the competing nature of magnetic interactions between the Ni NPs and NiOx phases. The ferromagnetism at 10 K (for all the Ni implants) is related to the combined contribution of both phases, while the room temperature superparamagnetism at higher fluence is dominated by Ni NPs phase as confirmed by Ni L-3,L-2 XMCD measurements. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: ION-IMPLANTATION; OXIDE NANOPARTICLES; THERMAL-OXIDATION; SIO2